Assessment of efficacy and safety of UV-based therapy for psoriasis: a network meta-analysis of randomized controlled trials - Yajia Li; Ziqin Cao; Jia Guo; Qiangxiang Li; Wu Zhu; Yehong Kuang; Xiang Chen (Annals of Medicine, 2022)
Background Previous studies have proven that ultraviolet (UV)-based phototherapy, including UVB or psoralen UVA (PUVA), and their combination therapies, is effective for psoriasis treatment. Objective To compare the clinical efficacy and adverse events (AEs) of different UV-based phototherapy in psoriasis. Methods PubMed, Cochrane Library, Scopus and Embase were systematically searched. A random-effect model network meta-analysis with frequentist framework was performed, and results were reported as risk ratios (RRs) with 95% CI. The main variable for assessing effectiveness and safety are PASI 75 response and withdrawal due to AEs. Ranking effects were calculated by surface under the cumulative ranking analysis (SUCRA). Results Thirty-two studies involving a total of 2120 psoriasis patients were included in this network meta-analysis. Overall, no significant difference was reported with respect to withdrawal due to AEs or incidence of erythema. The relatively safest strategy was combined adjuvant therapy with PUVA (cPUVA), especially PUVA combined with calcium/vitamin D derivatives (RR 0.98, 95% CI [0.30–3.17], SUCRA = 80.8%). Both cPUVA (RR 1.39, 95% CI [1.00– 1.94]) and combined adjuvant therapy with UVB (cUVB) (RR 1.27, 95% CI [1.03–1.57]) showed a superior effect than the monotherapy of UVA or UVB, respectively. PUVA combined with vitamin D and its derivatives (PAVD) ranked highest concerning clinical effect and safety (clusterank value = 7393.2). Conclusions The efficacy of all the combination therapy regimens was significantly superior to that of UV monotherapy, without significant differences in tolerability and safety. cUVB and cPUVA, and particularly the combination of UVA with calcium/vitamin D derivatives, was ranked as the overall safest and most effective phototherapy method.